2023
DOI: 10.1038/s41419-023-05602-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of systemic inflammation response index are correlated with tumor-associated bacteria in colorectal cancer

Abstract: The relationship between systemic inflammation and tumor-associated bacteria is largely unknown in colorectal cancer (CRC). The primary aim of this study was to investigate the prognostic effects of the systemic inflammation response index (SIRI) on the survival outcomes of CRC patients who experienced surgical therapy, and the second aim was to reveal the potential association between SIRI levels and tumor-associated bacteria in CRC. We recruited a cohort of 298 CRC patients who experienced surgical resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Subsequent studies have affirmed the association of SIRI with survival in patients with liver, gastric, nasopharyngeal, and breast cancers [19][20][21]. Moreover, Cao et al found that high preoperative SIRI was significantly associated with poorer OS and DFS of CRC patients, and predictive ability for the survival of CRC patients was superior to other inflammatory biomarkers, such as PLR, NLR, and SII [14]. However, to date, However, to date, multi-center data still need to confirm its relationship with CRC patients' survival adequately.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent studies have affirmed the association of SIRI with survival in patients with liver, gastric, nasopharyngeal, and breast cancers [19][20][21]. Moreover, Cao et al found that high preoperative SIRI was significantly associated with poorer OS and DFS of CRC patients, and predictive ability for the survival of CRC patients was superior to other inflammatory biomarkers, such as PLR, NLR, and SII [14]. However, to date, However, to date, multi-center data still need to confirm its relationship with CRC patients' survival adequately.…”
Section: Discussionmentioning
confidence: 96%
“…The systemic inflammation response index (SIRI) was established based on neutrophils, monocyte and lymphocyte. To date, the prognostic value of SIRI has been confirmed for various malignancies, such as pancreatic, cervical and gastric cancers, with limited evidence indicating a significant association with survival outcomes in CRC patients [11][12][13][14]. In addition, carcinoembryonic antigen (CEA) is a common tool used to evaluate the prognosis of CRC, and high preoperative CEA levels predict poor disease-free survival (DFS), overall survival (OS) and increased risk of recurrence and metastasis, as shown in earlier studies [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Some high-impact studies have collected FFPE as experimental samples to explore the relationship between tumor microbiota and cancer development, providing further support for the reliability of our approach and results ( 10 ). Cao et al ( 11 ) collected 166 paraffin-embedded tumor tissues and 24 frozen tumor tissues to investigate the prognostic effects of the systemic inflammation response index on the survival of colorectal cancer patients. Similar results were obtained in 16S rRNA based on the two different samples.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that have discussed the effects of SIRI on colorectal cancer patient’s prognosis. Cao et al evaluated the correlation of SIRI with tumor-associated bacteria and the prognosis of colorectal cancer patients [ 25 ]. They reported that SIRI had a superior predictive performance than the other inflammation-related markers, such as NLR, PLR, and LMR.…”
Section: Discussionmentioning
confidence: 99%